A New Approach For A Dual-Polarized Low Cost Patch Antenna With Low Cross- Polarization, High Bandwidth And High Isolation - Stöckle, Andreas; Lutz, Steffen; Talai, Armin; Fischer, Georg (IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications, 2014)
In this paper a new approach for a dual- polarized broadband patch antenna is presented. A novel feeding approach enables a high -10dB band- width up to 21 % as well as an isolation more than -29 dB. The realized antenna gain is > 6 dBi in the frequency range of 1320 MHz to 1680 MHz. Addi- tional, due to the re ector shaping, a low back ra- diation is achieved. Since standard components and FR4 material are used, the antenna concept enables an e ective low cost antenna production.
elib2cris::1512001600,stoeckle2014